Minute time scale prolyl isomerization governs antibody recognition of an intrinsically disordered immunodominant epitope - Fassolari, Marisol (2013)
Conformational rearrangements in antibody·antigen recognition are essential events where kinetic discrimination of isomers expands the universe of combinations. We investigated the interaction mechanism of a monoclonal antibody, M1, raised against E7 from human papillomavirus, a prototypic viral oncoprotein and a model intrinsically disordered protein. The mapped 12-amino acid immunodominant epitope lies within a "hinge" region between the N-terminal intrinsically disordered and the C-terminal globular domains. Kinetic experiments show that despite being within an intrinsically disordered region, the hinge E7 epitope has at least two populations separated by a high energy barrier. Nuclear magnetic resonance traced the origin of this barrier to a very slow (t(1/2)∼4 min) trans-cis prolyl isomerization event involving changes in secondary structure. The less populated (10%) cis isomer is the binding-competent species, thus requiring the 90% of molecules in the trans configuration to isomerize before binding. The association rate for the cis isomer approaches 6 × 10(7) M(-1) s(-1), a ceiling for antigen-antibody interactions. Mutagenesis experiments showed that Pro-41 in E7Ep was required for both binding and isomerization. After a slow postbinding unimolecular rearrangement, a consolidated complex with K(D) = 1.2 × 10(-7) M is reached. Our results suggest that presentation of this viral epitope by the antigen-presenting cells would have to be "locked" in the cis conformation, in opposition to the most populated trans isomer, in order to select the specific antibody clone that goes through affinity and kinetic maturation.